Analisis dan Perancangan Sistem Administrasi Pembayaran Siswa dengan Metode Human Centered Design (Studi Kasus: SMA Negeri 1 Sukodadi) - Alif Hilyatun Nisak; Satrio Hadi Wijoyo; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Student of SMA Negeri 1 Sukodadi increased every year. So, the needs of administration services about students payment increased too. This school already has a payment administration system. When the system is ready to use, East Java provincial government changed the regulation of Sumbangan Pembinaan Pendidikan (SPP) payment. Consequently, the system is unused because it does not match with the current user needs. The problem in the payment of participation are the management of administration still manual, the limitations of HR Manager of payment administration, and the process of income payment calculation is not time efficiency. Human Centered Design (HCD) is used method. The stages in HCD are context analysis and user needs by interview method. Results of this analysis are two users as respondents and user wants a new design that complies with rules to make it easier to manage payments and report generation. Design interfaces and solution designs generated wireframes and prototypes. Evaluation of prototypes using usability testing with effectiveness, efficiency, and satisfaction aspects. This evaluation is done by testing task scenario to determine the effectiveness and efficiency aspects. The satisfaction aspect is determined by the interview method to the user. The result of prototype evaluation on effectiveness aspect is79,24%, while the efficiency aspect are respondent 1 is 90% and respondent 2 is 100%, and than the satisfaction aspect is 4 issues.